Here and elsewhere: Transposed deities, substitute pilgrimages and geographic imagination in North India - Lazzaretti, Vera (Ethno-Indology, 2025)
Here and Elsewhere offers a grounded study of crucial modes of sanctification and imagination of Hindu geographies: spatial transposition and substitute pilgrimage. It looks at the local representatives of the pan-Indian jyotirliṅgas in Varanasi (Banaras) and the urban pilgrimage connected to them by combining interpretative analysis of glorifications (māhātmyas) with in-depth ethnographic research. This enables the author closely to observe the strategies that a variety of social actors employ to knit together and reproduce connections between places of the here and the elsewhere, and to locate deities and themselves within multiple spatial dimensions, both lived and imagined.